2019
DOI: 10.3390/sym11060727
|View full text |Cite
|
Sign up to set email alerts
|

Vibration Analysis of a Guitar considered as a Symmetrical Mechanical System

Abstract: This paper aimed to use the symmetry that exists to the body of a guitar to ease the analysis behavior to vibrations. Symmetries can produce interesting properties when studying the dynamic and steady-state response of such systems. These properties can, in some cases, considerably decrease the effort made for dynamic analysis at the design stage. For a real guitar, these properties are used to determine the eigenvalues and eigenvectors. Finite element method (FEM) is used for a numerical modeling and to prove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…These generate higher harmonics. The dynamics of the guitar body differs from that of the individually analyzed plates presented in previous papers [34,36,37]. This is due to the new bordering conditions created by attaching the sides to the top and back plates, as well as due to the aerodynamic phenomena inside the cavity that leads to delaying the transmission of vibration from the top plate to the backplate and to the sides [17,39].…”
Section: Fea Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These generate higher harmonics. The dynamics of the guitar body differs from that of the individually analyzed plates presented in previous papers [34,36,37]. This is due to the new bordering conditions created by attaching the sides to the top and back plates, as well as due to the aerodynamic phenomena inside the cavity that leads to delaying the transmission of vibration from the top plate to the backplate and to the sides [17,39].…”
Section: Fea Results and Discussionmentioning
confidence: 99%
“…The eigenmodes can be classified into two classes: symmetrical and skew-symmetrical eigenmodes. The properties of the symmetric systems were less used in the field of applied mechanics, but some papers study applications in the field [32][33][34].…”
Section: The Mathematical Model Of the Guitar As A Symmetrical Systemmentioning
confidence: 99%
“…The statistics of papers called for this Special Issue related to published or rejected items were [7][8][9][10][11][12][13][14][15][16][17][18][19][20]: total submissions (21), published (13; 62%), and rejected (8; 38%). The authors' geographical distribution by countries of authors in published papers is shown in Table 1, and it can be seen that 35 authors are from 11 different countries.…”
Section: Statistics Of the Special Issuementioning
confidence: 99%